GTP cyclohydrolase I gene transfer augments intracellular tetrahydrobiopterin in human endothelial cells: effects on nitric oxide synthase activity, protein levels and dimerisation. - Cai, S; Alp, N; McDonald, D; Smith, I; Kay, J; Canevari, L; Heales, S; Channon, K (2002)
OBJECTIVES: Tetrahydrobiopterin (BH4) is an essential cofactor for endothelial nitric oxide synthase (eNOS) activity. BH4 levels are regulated by de novo biosynthesis; the rate-limiting enzyme is GTP cyclohydrolase I (GTPCH). BH4 activates and promotes homodimerisation of purified eNOS protein, but the intracellular mechanisms underlying BH4-mediated eNOS regulation in endothelial cells remain less clear. We aimed to investigate the role of BH4 levels in intracellular eNOS regulation, by targeting the BH4 synthetic pathway as a novel strategy to modulate intracellular BH4 levels. METHODS: We constructed a recombinant adenovirus, AdGCH, encoding human GTPCH. We infected human endothelial cells with AdGCH, investigated the changes in intracellular biopterin levels, and determined the effects on eNOS enzymatic activity, protein levels and dimerisation. RESULTS: GTPCH gene transfer in EAhy926 endothelial cells increased BH4 >10-fold compared with controls (cells alone or control adenovirus infection), and greatly enhanced NO production in a dose-dependent, eNOS-specific manner. We found that eNOS was principally monomeric in control cells, whereas GTPCH gene transfer resulted in a striking increase in eNOS homodimerisation. Furthermore, the total amounts of both native eNOS protein and a recombinant eNOS-GFP fusion protein were significantly increased following GTPCH gene transfer. CONCLUSIONS: These findings suggest that GTPCH gene transfer is a valid approach to increase BH4 levels in human endothelial cells, and provide new evidence for the relative importance of different mechanisms underlying BH4-mediated eNOS regulation in intact human endothelial cells. Additionally, these observations suggest that GTPCH may be a rational target to augment endothelial BH4 and normalise eNOS activity in endothelial dysfunction states.